The engines of European integration delegation, agency, and agenda setting in the EU - Pollack, Mark A., 1966-; Oxford eBooks (Oxford : Oxford University Press, 2003)
This study of delegation and agency in the European Union examines the role of supranational actors like the Commission the Court of Justice, and the European Parliament in the process of European integration and in contemporary EU governance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; Delegation of powers -- European Union countries; Europe -- Economic integration; Electronic books